Combination of autoimmune hepatitis to non-alcoholic steatohepatitis (Clinical case) - A. A. Driga; M. V. Mayevskaya; V. T. Ivashkin (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
The aim of publication. To describe clinical case with a rare combination of two diseases which developed almost asymptomatically for a long time: autoimmune hepatitis (AIH) of the 1-st type and non-alcoholic steatohepatitis (NASH) on a background of morbid obesity, 2-nd type diabetes mellitus and dyslipidemia. To demonstrate efficacy of budesonide treatment in combination to the lifestyle modification directed to weight loss that resulted in normalization of biochemical scores and improvement of histological liver pattern.The basic contents. Presented clinical case shows a rare combination of high-activity asymptomatic autoimmune hepatitis of 1-st type of long duration with non-alcoholic steatohepatitis in a patient with morbid obesity. Drug effect was a trigger factor for clinical manifestation of disease. Activity of serum transaminases acutely increased following metformin dose increase and onset of intravenous infusions of α-lipoic acid (thiogamma) in patient with 2-nd type diabetes mellitus. In physical status asthenia, body mass index of 49,8 kg/m2, subicteric sclerae drawn attention. Blood pressure was 130/90 mm Hg, patient had hepatomegaly (+5 cm). Abdominal ultrasonography revealed liver and pancreatic steatosis. Specific tests excluded presence of viral hepatitis, hemochromatosis, Wilson disease and α1-antitrypsin insufficiency. Antismooth muscles antibodies titer was 1:40. Liver biopsy was executed for suspicion of NASH: histological activity index (HAI) was 14 points (4+3+4+3) with severe fibrosis, no fatty infiltration was revealed. According to international classifications the 1-st type AIH of high activity (triggered by medicinal factor) in combination to NASH on a background of morbid obesity (dyslipidemia: cholesterol – 198 mg/dl, very low and high-density lipoproteins 38,2 and 31,3 mg/dl respectively) was diagnosed. Treatment included budenofalk 9 mg per day, that was followed by normalization of transaminases within 3 months. Self-directed cancellation of treatment resulted in relapse. Liver biopsy was repeated: HAI was 10 points (3+1+3+3), hydropic, small and large droplet fatty dystrophy, moderate fibrosis. Clinical diagnosis was following: AIH of 1-st type with high degree of activity, NASH with severe fibrosis, second type DM in compensated phase, morbid obesity, dyslipidemia, systemic hypertension («metabolic syndrome»). Repeated prescription of budenofalk in a dose of 9 mg in combination to diet and weight loss resulted in normalization of serum transaminases.Conclusion. Both autoimmune hepatitis, and nonalcoholic steatohepatitis can develop asymptomatically for a long time and result in severe liver fibrosis that is illustrated by presented clinical case. Efficacy of budesonide allows to assume improvement of disease and life prognosis at the observed patient. Modification of lifestyle directed to weight loss, results in more favorable course of non-alcoholic steatohepatitis that can be presumed by liver histological data (decrease of inflammatory activity degree in comparison to initial biopsy specimen).